2010
DOI: 10.1111/j.1462-5822.2009.01409.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivobiofilm composition ofAspergillus fumigatus

Abstract: SummaryThe in vivo composition of the mycelial extracellular matrix (ECM) of Aspergillus fumigatus during host invasion is reported here for the first time. A new galactosaminogalactan and the galactomannan were the major polysaccharides of the in vivo ECM. The composition of the ECM in vivo varied with the aspergillosis pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
264
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(275 citation statements)
references
References 22 publications
5
264
0
6
Order By: Relevance
“…In addition, these fungi have been implicated in central-venous-catheter-associated fungaemia (Chan-Tack et al, 2005), peritonitis in patients undergoing continuous ambulatory peritoneal dialysis (Branton et al, 1990;Fergie et al, 1992;Nakamura et al, 1989;Nannini et al, 2003;Nayak et al, 2007;Polo et al, 1989;Serna et al, 2003), pleuritis following implantation of drainage catheters (Kimura et al, 2009), endocarditis on native (Mehta et al, 2004;Mitchell et al, 2010) and artificial heart valves (Gubarev et al, 2007;Sanchez-Recalde et al, 1999), osteomyelitis (Chaudhuri et al, 1992;Eaton et al, 1994;Lopes et al, 1995;Meis et al, 1994;Wilkins et al, 2009), and paranasal fungal balls (Goodnight et al, 1993;Kirkpatrick et al, 1979;Lahiri et al, 2001;Robey et al, 2009). Many of these infections are associated with biofilm formation (Costerton et al, 1999;Hall-Stoodley et al, 2004;Loussert et al, 2010) and were reported to exhibit a chronic course (Eaton et al, 1994;Lahiri et al, 2001;Lopes et al, 1995). Furthermore, surface-attached growth of zygomycetes has often been used for industrial purposes (Cao et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, these fungi have been implicated in central-venous-catheter-associated fungaemia (Chan-Tack et al, 2005), peritonitis in patients undergoing continuous ambulatory peritoneal dialysis (Branton et al, 1990;Fergie et al, 1992;Nakamura et al, 1989;Nannini et al, 2003;Nayak et al, 2007;Polo et al, 1989;Serna et al, 2003), pleuritis following implantation of drainage catheters (Kimura et al, 2009), endocarditis on native (Mehta et al, 2004;Mitchell et al, 2010) and artificial heart valves (Gubarev et al, 2007;Sanchez-Recalde et al, 1999), osteomyelitis (Chaudhuri et al, 1992;Eaton et al, 1994;Lopes et al, 1995;Meis et al, 1994;Wilkins et al, 2009), and paranasal fungal balls (Goodnight et al, 1993;Kirkpatrick et al, 1979;Lahiri et al, 2001;Robey et al, 2009). Many of these infections are associated with biofilm formation (Costerton et al, 1999;Hall-Stoodley et al, 2004;Loussert et al, 2010) and were reported to exhibit a chronic course (Eaton et al, 1994;Lahiri et al, 2001;Lopes et al, 1995). Furthermore, surface-attached growth of zygomycetes has often been used for industrial purposes (Cao et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Aspergilloma, a localized infection, has been shown to consist of highly agglutinated hyphae encased in an extracellular matrix (Loussert et al, 2010;Mowat et al, 2009). A similar exopolysaccharide matrix is also produced at the surface of fungal hyphae during invasive pulmonary aspergillosis (Loussert et al, 2010 and fungal-ball formation (Chakrabarti et al, 2001(Chakrabarti et al, , 2006(Chakrabarti et al, , 2009Goodnight et al, 1993;Kirkpatrick et al, 1979;Lahiri et al, 2001;Robey et al, 2009). Mucormycosis is categorized into rhino-orbito-cerebral (ROC), pulmonary, gastrointestinal, cutaneous and disseminated types depending upon the clinical presentation and the anatomical sites involved (Chakrabarti et al, 2001(Chakrabarti et al, , 2006(Chakrabarti et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…S imilar to biofilm-forming bacteria or yeasts (1), Aspergillus fumigatus, the most prevalent airborne fungal pathogen (2), is now largely acknowledged to be an organism able to grow and develop as a multicellular community (3), in which the hyphae are cohesively bonded together by a hydrophobic extracellular matrix (ECM) (4), under the aerial and static conditions found by the fungus either in vitro or in vivo (5)(6)(7)(8)(9). This growth phenotype, which complies with the definition of a biofilm (10), may help A. fumigatus to colonize the host substratum and to resist phagocytic and antimicrobial attacks, mimicking the typical Candida albicans or bacterial biofilm (8,11).…”
mentioning
confidence: 99%